Should I stay or should I go? The effect of NIL and transfer rule changes on college basketball players entering the NBA draft - McDaniel, C.; Meehan, B.; Frank Stephenson, E. (Journal of Sports Economics, 2025)
We examine the impact of name, image, and likeness (NIL) opportunities and changes in transfer rules on the NBA draft decisions of men's college basketball players. The National Collegiate Athletic Association's 2021 liberalization of NIL and transfer eligibility rules enhanced college athletes` earning potential, thereby possibly influencing their draft entry decisions. Analyzing college players among the top 100 prospects for each draft year between 2019 and 2024, we find that, following the NIL and transfer rule changes, more college players chose to forgo the draft and use the remaining collegiate eligibility. Our findings show a larger impact on players projected to be drafted outside of the first round and that the effect of the NIL and transfer rule changes has grown over time.